IMPLEMENTASI PERATURAN GUBERNUR JAWA BARAT NOMOR 16 TAHUN 2019 PADA PPDB BAGI ANAK BERKEBUTUHAN KHUSUS DI SMA NEGERI DI KABUPATEN BANDUNG - Widya Puspa Amalia, - (2020)
In 2019, the Regional Government of West Java Province made a policy on New Student Admission Program (PPDB) for Special-needs children in Senior High School (SMA) level. This is regulated in Governor Regulation of West Java Number 16 of 2019. This research aims to determine the implementation of the said regulation on PPDB for children with Special-needs in state senior high schools in Bandung Regency. The research design used is descriptive Qualitative. The research sites are six state senior high schools in Bandung Regency. The data were collected using interview techniques, document review, and online data search. The data obtained were then validated using triangulation techniques and member checks. The data analysis consists of data reduction, data display, and data verification. The result showed that most of the schools had implemented the regulation by opening registration and providing quotas for the Special-needs children. The result of the implementation was proven by the acceptance of students through PPDB for children with Special-needs. There are four factors which support the implementation of PPDB for Special-needs children in Senior High School level, namely communication, resources, disposition and bureaucratic structure. The obstacles occurring in the implementation are that there were still prospective students who did not get enough information because the information was published virtually, there was no socialization to special schools, and there was no committee who was expert in special education. The effort of education unit to solve the problem is by opening offline information services and discussing with parents, counselling teachers, or a team of experts in the related field.